Produção de proteínas semelhantes à imunoglobulina leptospiral fundidas às proteínas ZZ e/ou domínios R e/ou do HIV-1 TAT - Monaris, D.; Savatier, A.; Ho, P. L.; Léonetti, M.; Abreu, P.A.E. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2019)
Leptospirosis is a zoonotic disease caused by pathogenic spirochetes of the genus Leptospira which colonize the renal tubules of wild or domestic animals and are released to the external environment in urine. The development of a vaccine is very important, since the control of carrier animals is difficult. Some vaccines are being used, but they promote protection only against the serotypes present in the preparation and fail to induce long- term immunity. The LigA and LigB proteins are able to induce immunoprotection against leptospirosis, however, it didn’t confer sterilizing immunity.